Ralph Wormeley correspondence - Wormeley, Ralph, 1744-1806.
ALS (1782 April 19; Rosegill [Middlesex County, Va.]) from Wormeley to John Robinson regarding the purchase of slaves.
Loyalist, member of the Virginia House of Delegates, and scholar.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Slavery -- United States; Slaves -- Virginia; Middlesex County (Va.) -- History; American loyalists; Legislators -- Virginia; Scholars